The Impact of Metacognitive Practices on 6th Grade Students’ Engagement and Academic Performance - MNADLA, Sofiane; ZOGHLMI, Wael; RAHALI, Ghada; ELLOUMI, Ali; JLASSI, Aicha (Journal of Posthumanism, 2025)
This study focuses on the impact of metacognitive practices on students’ engagement and academic performance. To collect the necessary data, an experiment was conducted with sixth-grade primary school students. It consisted of a series of activities supported by a metacognition worksheet and self-administered questionnaires designed to assess students’ levels of engagement before and after the implementation of metacognitive practices. In addition, semi-structured interviews were conducted with primary school inspectors to gain deeper insight into the role of metacognition in the school context. The analysis of the collected data, using both qualitative and quantitative approaches, revealed correlations between metacognitive practices, student engagement, and academic performance. The findings highlight the importance of fostering metacognition from an early age to promote autonomous, confident, and reflective learners. This research therefore underscores the need to integrate metacognition into pedagogical strategies to enhance students’ involvement in their learning journey.